Development of Adobe Flash-Based Multimedia in Learning Recognition of Parts of Human Body - Farida Febriati; Nurhikmah H; Andi Akram Dolla (AL-ISHLAH: Jurnal Pendidikan, 2022)
The learning process in the classroom is difficult for students to understand the material being taught, because learning does not apply learning material in using media in the classroom environment, so the learning process in class is not effective in understanding the material being taught. This study aims to identify a description of the need for developing multimedia learning of human limb recognition using Adobe Flash, designing multimedia for learning human limb recognition using Adobe Flash, measuring the level of validity and practicality of multimedia for learning human limb recognition using Adobe. This research is a type of RD (Research and Development) used ADDIE model (analysis, design, development, implementation, evaluation). The results showed that Adobe Flash-based multimedia products were valid to be used based on the results of validation by content/material experts obtaining a percentage result of 100% being in very good qualifications, validation results by design experts obtaining a percentage of 86% being in good qualifications, validation results by media experts obtained a percentage result of 94% being in very good qualifications, then in practicality trials conducted on students who obtained results 98.17% were in very good qualifications, and the responses of subject teachers related to Adobe Flash-based multimedia obtained 100% results which were in very good  qualification. Based on the results of the analysis, it can be concluded that Adobe Flash-based multimedia is valid and practical to use in the learning process of Education, Physical, Sports and Health subjects.